Brexit: lessons learned, status quo and way ahead - Okinčic, Sebastjan (Vilnius University Open Series, 2020)
On 23 June 2016 almost 17.5 million citizens of the United Kingdom voted to leave the European Union. The UK government invoked the relevant Article 50 of the Treaty on European Union on 29 March 2017. As authors of the said provision have admitted, it was never to be used (Fabbrini, 2017). And yet here we all are/were (depending on when you are reading it), anno domini 2020, witnessing an unprecedented event of a sovereign state “taking back control” i.e. leaving in great pain the most powerful economic and political union of sovereign states ever established, taking advantage of the procedure that had initially not only been de iure impossible, but also seemed inconceivable in and of itself. According to Theresa May, “Brexit means Brexit”. Little help did that tautological definition bring anyone. And yet, after Brexit came, the transition period started. Written in the middle of the said transition period, the purpose of this paper is to briefly treat on Brexit in general and the near-term future related thereto. In addition, also considering the timing of this paper, i.e. May / June 2020, a particular regard will be paid to the more distant future ahead of us – certain matters pertaining to international commercial dispute resolution after Brexit. Considering the overall uncertainty surrounding Brexit that we find ourselves in, the relevance of the topic discussed in the paper is unquestionable. In addition, relevance-wise, one could consider whether the process we are all witnessing could result in encouraging or, rather, discouraging any similar future initiatives. In this context, a broader perspective will be utilised to come to certain indicative conclusions as to whether Brexit can result in good know-how practices learned for future similar initiatives, or rather serve as an example for “never again”.